Perfectionism is associated with higher eating disorder symptoms and lower remission in children and adolescents diagnosed with eating disorders - Johnston, J.; Shu, C.; Hoiles, K.; Clarke, Patrick; Watson, H.; Dunlop, P.; Egan, Sarah (Pergamon, 2018)
© 2018 Objective: The link between perfectionism and eating disorders is well established in adults, however little research has been conducted in children and adolescents. The aim was to examine if perfectionism was a predictor of eating disorder symptoms at intake assessment, and 6 and 12 month review. Method: There were 175 children and adolescents aged 10–17 years (M = 14.47 years, SD = 1.31) who were assessed using the Eating Disorders Inventory-3 perfectionism subscale and the child adapted Eating Disorders Examination at intake, 6 and 12 months review. Results: There was a significant association between perfectionism and symptoms of eating disorders at intake assessment and at 6 and 12 month review. Higher perfectionism at intake predicted a lower likelihood of remission at 12 months. Discussion: The findings suggest that similar to adult samples, perfectionism is significantly associated with eating disorder symptoms in children and adolescents. Further research is required to examine the impact of perfectionism on eating disorder symptoms in longitudinal research with children and adolescents with eating disorders.